The positive association between perceived parental responsiveness and self-esteem, anxiety, and thriving among youth rugby players: A multigroup analysis. Issue 13 (3rd July 2021) - Rouquette, Olivier Y.; Knight, Camilla J.; Lovett, Victoria E.; Barrell, Donald; Heuzé, Jean-Philippe
ABSTRACT: The purpose of this study was to examine the association between young players' perception of mother's and father's responsiveness with their self-esteem, anxiety (i.e., worry), and thriving (i.e., positive affect, vitality, and life satisfaction). In total, 314 male British rugby players with a mean age of 16.23 years ( SD = 0.26) completed the study in two phases: n = 124 (first dataset), and n = 192 (second dataset). Participants trained on average 3.14 times/week ( SD = 0.94) and had been involved in rugby for an average of 8.21 years ( SD = 2.89). Participants completed questionnaires measuring perceived parental responsiveness (PPR) for their mother and father, self-esteem, worry about sport performance, and thriving indicators (i.e., positive affect, vitality, and life satisfaction). The results consistently indicated that participants' perceptions of their mother's and father's responsiveness positively related to thriving, and negatively related to their worry about sport performance, mediated by their self-esteem. Overall, the study highlights the need for parents to be provided with insights into the value of being responsive to their child and being encouraged to regularly talk with their child regarding their needs and desires, and seeking to understand how their child perceives the support they currently receive.